AB0543 Factors associated with work disability in patients with ankylosing spondylitis. (23rd January 2014) - Castillo-Ortiz, J. D.; Ramiro, S.; Landewé, R.; van der Heijde, D.; Dougados, M.; van den Bosch, F.; Boonen, A.
Abstract : Background: Ankylosing Spondylitis (AS) usually affects patients in early years of life, when the professional career is one of the individual's primary social roles. In addition, work disability (WD) represents the major driver of the total cost-of-illness of the disease. Objectives: To describe and to explore WD in a cohort of patients with AS, as well as their associated factors, and to compare the prevalence of WD in AS with the one of the general population. Methods: Data on work outcome and clinical characteristics were obtained from patients followed in the Outcome in AS International Study (OASIS) which included patients from the Netherlands, France and Belgium. Data from the baseline assessment were used. Logistic regression (univariable followed by multivariable) was used to investigate factors associated with WD. Prevalence of work disability in Dutch patients included in OASIS and with working age (n=130) was compared with the one of the general population (source: official statistics office, cbs.nl) through indirect standardization adjusting for age and gender. Comorbidity was tested as independent variable using comorbidity index (range 0-9, the higher the more comorbidities). Results: Of 215 patients included in this study (mean age 43.5 (SD12.5) years, mean disease duration 11.4 (SD 9.1) years, 71 % male, 80% HLA-B27), 26% (n=55) were full-work disabled and 58% (n=124) were working at baseline. In multivariable analysis older age (OR 1.08; 95% CI 1.02-1.13), Dutch origin (OR 4.59; 95% CI 1.25-16.85), high comorbidity index (OR 2.31; 95% CI 1.13-4.7), poor function, i.e. higher BASFI (OR 1.49; 95% CI 1.19-1.88) and high disease activity, i.e. ASDAS (OR 2.01; 95% CI 1.08-3.72) were significantly associated with WD (Table ). The risk for being WD among Dutch patients (n=130, of which 47 were WD) was 5.6 (95% CI 4.1-7.1) for males and 6.4 (95% CI 3.6-9.14) for females, times higher than expected compared to general population. Conclusions: In this prevalence cohort of patients with AS, the prevalence of WD is quite high (26%). Among Dutch patients in working age the risk of WD was 6 times higher than the expected risk. Not only disease related variables (function, activity and comorbidity), but also contextual factors (age and Dutch origin) were significantly associated with WD. Disclosure of Interest: None Declared